The Effect of Online Corrective Feedback (OCF) on Learners’ Relative Clauses Competency - Hendrayana, Afdal Ade (Postgraduate School, Universitas Negeri Padang, 2025)
The study explored the use of OCF for giving feedback in constructing relative clauses for Indonesian English learners. Using a quasi-experimental design, the sample covers 47 learners. The two classes were randomly assigned as the experiment group (N=25) using the OCF method and the control group (N=22) with the conventional one. Pre- and post-tests were given by asking learners to construct two sentences into relative clauses based on the theory of English grammar (Azar, 1998; 2009). The independent sample t-test and Mann-Whitney U test with the SPSS software program were used to analyze the data. The result revealed there was a statistically significant score difference.